2000
DOI: 10.1038/sj.onc.1203674
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus-X protein upregulates the expression of p21wafl/cipl and prolongs G1→S transition via a p53-independent pathway in human hepatoma cells

Abstract: Progression through the cell cycle is controlled by the induction of cyclins and activation of cognate cyclindependent kinases. The human hepatitis B virus-X (HBV-X) protein functions in gene expression alterations, in the sensitization of cells to apoptotic killing and deregulates cell growth arrest in certain cancer cell types. We have pursued the mechanism of growth arrest in Hep3B cells, a p53-mutant human hepatocellular carcinoma (HCC) cell line. In stable or transient HBV-X transformed Hep3B cells, HBV-X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 43 publications
(43 reference statements)
2
59
0
1
Order By: Relevance
“…Inversely, HBx enhanced p21 in some reports [34,35] . Park et al [34] reported that when the cell cycle was prolonged by enhancement of p21 by HBx, cells had survival advantages and chances for gene mutations, eventually leading to preneoplastic hepatocytes. In addition, Yano et al [36] reported that HBx enhanced cytoplasmic p21 in protein kinase C (PKC)-dependent manner to induce cell proliferation.…”
Section: Hcc Hbx and P21mentioning
confidence: 99%
“…Inversely, HBx enhanced p21 in some reports [34,35] . Park et al [34] reported that when the cell cycle was prolonged by enhancement of p21 by HBx, cells had survival advantages and chances for gene mutations, eventually leading to preneoplastic hepatocytes. In addition, Yano et al [36] reported that HBx enhanced cytoplasmic p21 in protein kinase C (PKC)-dependent manner to induce cell proliferation.…”
Section: Hcc Hbx and P21mentioning
confidence: 99%
“…MMP-7 expression is also up-regulated in early, di erentiated tumor cells, promoting angiogenesis and the intrahepatic spread of tumor. The ®nding that bcatenin and the Ets oncoprotein stimulate of MMP-7 expression (Ozaki et al, 2000), and that HBxAg transactivation maps to Ets binding sites on cellular genes (Park et al, 2000), implies that HBxAg may modulate the outgrowth of early HCC by de®ning the integrity of the extracellular matrix during chronic infection.…”
Section: Early Events In Hepatocarcinogenesismentioning
confidence: 99%
“…In some established cell lines and in mouse primary hepatocyte cultures, HBx alters expression of p21 and p27 cell cycle regulation genes, influencing cell cycle progression profiles in these cells (1,42,61,89,93). However, there are no clear answers as to whether HBx induces or inhibits expression of p21 and p27, as conflicting reports have been published; these differences may reflect influences of the experimental systems or levels of HBx expression (61,93).…”
Section: Hbx and The Cell Cyclementioning
confidence: 99%